Pengaruh Variasi Arus dan Tegangan pada Kinerja Motor Pompa Dosing di Perumdam Tirta Madani Kota Serang - Ismah Nurul Sya’bani (Pusat Riset dan Inovasi Nasional, 2025)
One of the factors that can affect the performance of a dosing pump motor is the current and voltage supplied to the motor. Optimal variations in current and voltage can increase the fluid flow rate and dosing accuracy, while mismatches can lead to instability during operation. This experiment aims to reveal how changes in current and voltage affect the performance and efficiency of a dosing pump motor. The method used for data collection is an experiment on the observed object, namely a three-phase 380 Volt, 60 Hz, 3360 rpm induction motor of a dosing pump, by conducting tests and measurements of current, voltage, power, and stroke adjustment (valve) variation on the dosing pump during production. Based on the results, at a valve angle of 10°, the lowest setting, the voltage was 360 V and the current was 1.8 A, producing a motor power output of 102.8 Watts and a power factor of 0.42. When the valve was increased to 100°, the voltage was 380 V and the current rose to 5.70 A, resulting in a power output of approximately 2,166 Watts and a power factor of 0.0384, indicating that the motor's efficiency did not reach a power factor of 1. The variation in stroke adjustment (valve) on the dosing pump motor affects the current, voltage, and power output of the motor. Higher current and voltage are required by the motor to drive the dosing pump, as pumping fluid at a higher flow rate requires more power.